Resonant-enhanced above-threshold ionization of atoms by XUV short laser pulses - Rodriguez, V. D. (2009)
Above-threshold ionization of atoms by XUV short laser pulses is investigated close to the resonant 1s–2p transitions. Both ab initio TDSE and a theoretical Coulomb–Volkov like theory are used to study the enhancement in the ionization probabilities. Our modified Coulomb–Volkov theory, fully accounting for the important 1s–2p transition is able to explain the spectrum as well as the total ionization cross sections.